Utilization of the Artificial Intelligence-Based Teachy Application to Improve the Efficiency of Junior High School Teachers' Administrative Tasks - Karnaen, Karnaen; Iqbal, Muh.; Asra, Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to analyze the increase in the efficiency of teachers' administrative tasks before and after using the artificial intelligence (AI)-based Teachy application at SMP Negeri 1 Poli-Polia. The main problem underlying this study is the high burden of teachers' administrative learning, which results in limited time for developing innovative and student-centered learning. This study uses a quantitative approach with a quasi-experimental design through a one-group pretest–posttest model. The research subjects involved all 18 teachers at SMP Negeri 1 Poli-Polia, with a sampling technique using total sampling. Data were collected through a questionnaire on the efficiency of teachers' administrative tasks and learning device documentation, then analyzed using the N-gain test, paired t-test, and Wilcoxon test. The results showed that there was an increase in the efficiency of teachers' administrative tasks in the moderate category after using the Teachy application. In addition, there was a significant difference between the efficiency of teachers' administrative tasks before and after using the Teachy application, and the use of the Teachy application was proven to have a significant effect on the efficiency of teachers' administrative tasks. These findings indicate that the use of the AI-based Teachy application can be an effective solution in reducing the administrative burden on teachers and supporting improvements in the quality of learning management in junior high schools.